Prevalence of Obesity in Adolescents with History of Pregnancy and Associated Factors in Korea - Seong-Ik Baek; Wi-Young So (Tehran University of Medical Sciences, 2011)
Background: The pregnancy was a risk factor for excessive weight gain for women. However, there is no information about the prevalence of obesity and its relationship with a history of pregnancy in girls. Therefore, the purpose of this study was to investigate differences in the prevalence of obesity in adolescent females with a history of pregnancy and factors associated with it, in Korea.Methods: In 2009, 69 of 34,247 female students revealed that they had experienced pregnancy in response to the 5th Korea Youth Risk Behavior Web-based Survey (KYRBWS-V) project by the Korea Centers for Disease Control and Prevention (KCDCP). The body mass index (BMI) and experienced pregnancy categories of the KYRBWS-V were assessed, and, for data analysis, the independent t-test, chi-square test, and multivariate logistic regression were used.Results: The risk of pregnancy was increased by approximately 47% per unit increase in age, and 331% per unit increase in depression, respectively. Conversely, the risk decreased by 19% per unit increase in BMI and 33% per unit increase (ranged from 1: very rich to 5: very poor) in the family economic state.Conclusion: Obesity in adolescent females is minimally affected by a history of pregnancy, if at all, despite the fact that pregnancy was a risk factor for excessive weight gain in women. However, adolescent females with a history of pregnancy have higher levels of depression than do normal peers in Korea.